(untitled) (International Journal of Engineering and Computer Science, 2015)
A self-optimizing network is an effective method for network management and maintenance in Long Term Evolution, which supports the co channel deployed heterogeneous networks and significantly increases the quality of service. The Zone based Load Balancing uses several game theoretic approaches to carry out load balancing but it results in uncoordinated load distribution among multiple cells. It may cause the problem of hidden cell case and slow convergence issues. Along with this problem the Nash Equilibrium used in game theory algorithm cannot be obtained, it may continuously finding solution for long duration. It can be solved by introducing the innovative method of meta heuristic search algorithm called Multi objective Bat Algorithm. It is very promising and could outperform the existing algorithms. The Multi Objective Bat algorithm combined with the priori expert knowledge reduces search space and computational time required for designing the MLB controller. The Multi Objective Algorithm provides the best optimization solution in short period of time and the problem of slow convergence time gets eliminated.